Potato Staple Food Processing Technology - Mu, Taihua; Sun, Hongnan; Liu, Xingli (SpringerBriefs in Food, Health, and Nutrition,, 2017)
This book introduces readers to volatile compounds of staple foods, while also systematically highlighting the processing technologies of potato staple foods, which will be of great importance in promoting the virtuous circle and structural upgrading of Potato consumption patterns are gradually changing from fresh to processed formulations, (e.g. mashed potatoes, potato chips, etc.) as a result of fast food habits adopted from developed countries. If the potato can be used to make staple foods, it will not only provide energy, but also nutrition. Though the book is primarily intended for researchers and students in the field of food technology, it will also be of interest to commercial research staff in food technology. .